Antibacterial effects of Traditional Chinese Medicine monomers against Streptococcus pneumoniae via inhibiting pneumococcal histidine kinase (VicK) - Zhang, Shuai; Wang, Jianmin; Xu, Wenchun; Liu, Yusi; Wang, Wei; Wu, Kaifeng; Wang, Zhe; Zhang, Xuemei (Frontiers in Microbiology, 2015)
Two-component systems (TCSs) have the potential to be an effective target of the antimicrobials. VicK/VicR is one of TCSs in S. pneumoniae, which is essential for pneumococcal survival. We have previously obtained serveal Traditional Chinese Medicine monomers using a computer-based screening. In this study, either alone or in combination with penicillin, their antimicrobial activities were evaluated based on in vivo and in vitro assays. The results showed that the MICs of 5'-(Methylthio)-5'-deoxyadenosine, octanal 2, 4-dinitrophenylhydrazone, deoxyshikonin, kavahin, and dodecyl gallate against S. pneumoniae were 37.1, 38.5, 17, 68.5, and 21 µg/mL, respectively. Time-killing assays showed that these compounds elicited bactericidal effects against S. pneumoniae D39 strain, which led to a 6-log reduction in CFU after exposure to compounds at four times of the MIC for 24 h. The five compounds inhibited the growth of S.pyogenes, S.mitis, S.mutans or S. pseudopneumoniae, meanwhile, deoxyshikonin and dodecyl gallate displayed strong inhibitory activities against S. aureus. Survival time of the mice infected by S. pneumoniae strains was prolonged by the treatment with the compounds. Importanly, all of the five compounds exerted antimicrobial effects against multidrug-resistant clinical strains of S. pneumoniae. Moreover, even at sub-MIC concentration, they inhibited cell division and biofilm formation. The five compounds all have enhancement effect on penicillin. Deoxyshikonin and dodecyl gallate showed significantly synergic antimicrobial activity with penicillin in vivo and in vitro, and effectively reduced nasopharyngeal and lung colonization caused by different penicillin-resistant pneumococcal serotypes. In addition, the two compounds also showed synergic antimicrobial activity with erythromycin and tetracycline. Taken together, our results our results suggested that these novel VicK inhibitors may be promising compounds against gram-positive bacterial infection.